Socialism and Alienation - Repšys, Jonas (Problemos, 1968)
The paper makes an attempt to raise the problem of correlation of socialism and alienation on the basis of Marxist methodology. First the paper reveals the scientific expedience and ideological significance of the analysis of socialist society from the point of view of alienation under present circumstances. The author attempts to show the essence of the Marxist understanding of the problem of alienation, i.e., the differences in the views of Hegel, Feuerbach and Marx concerning the problem. Alongside with this, modern “extensive” interpretations of the concept of alienation, often employed by Western philosophers to criticise socialism, are proved to be but a step backward as compared to Marx. The paper points out that the dispute among those who regard the problem of alienation as the main problem of socialism and those who maintain that alienation is not inherent in socialism “ex deflnitione”, oversteps the limits of the materialistic understanding of history and rests on the merely ethical plane. The paper also shows that socialism is the first stage in overcoming alienation in human relations in the economic, political, as well as cultural spheres. The analysis of socialism from the point of view of overcoming alienation is of areal importance for the further development of the system.